Essays on the economics of human trafficking, migration and remittances - Joarder, Mohammad Abdul Munim (Curtin University, 2014)
The thesis firstly deals with human trafficking and the migration-debt contract, theoretically and empirically, by paying particular attention to the organisational process of human trafficking. The second part deals with international migration and the consequent remittances using matched samples of Bangladeshi migrants living in the UK and Malaysia. It examines the determinants and motives to remit; and considers happiness functions to explore how remittances influence happiness among migrants and their left-behind households.